Self-Justification Processes Related to Bullying Among Brazilian Adolescents: A Mixed Methods Study - de Oliveira, Wanderlei Abadio; Caravita, Simona C. S.; Colombo, Barbara; Donghi, Elisa; da Silva, Jorge Luiz; Silva, Marta Angélica Iossi (Frontiers in Psychology, 2019)
This study aims to investigate the associations between bullying and moral disengagement in a Brazilian sample, using a mixed method design. Two-thousand three hundred and thirty-four adolescents (11-19 years; 42.9% girls) answered self-report measures on bullying and moral disengagement in response to bullying situations. Fifty-five participants were randomly selected and interviewed on their experiences on bullying at school. Results allowed to identify specific mechanisms of moral disengagement associated with bullying behavior among Brazilian adolescents. Qualitative analysis highlighted how moral disengagement mechanisms were spontaneously used by the adolescents to explain both the bullying and the bystander behaviors. Findings support the relevance of moral disengagement mechanisms in explaining bullying behaviors. The value of addressing these mechanisms when designing anti-bullying interventions is discussed.